Mekanisme Pengenaan Pajak Bea Perolehan Hak Atas Tanah Dan Bangunan (BPHTB) Pada Program Pendaftaran Tanah Sistematis Lengkap (PTSL) - Indra Lestari (Recital Review, 2023)
The purpose of this study is to find out and analyze imposition of land and building rights (BPHTB) acquisition fees on the complete systematic land registration program (PTSL). Second, mechanism for the Transfer of complete systematic land registration (PTSL) certificates of ownership to mortgage rights if the certificate of ownership is pledged as collateral to the Bank. Therefore, from these objectives, 2 problem formulations were formulated in this research, namely: First, How is the imposition of land and building rights (BPHTB) acquisition fees on the complete systematic land registration program (PTSL)? Second, How is the mechanism for the Transfer of complete systematic land registration (PTSL) certificates of ownership to mortgage rights if the certificate of ownership is pledged as collateral to the Bank? The theories used in this research are the theory of legal certainty, and the theory of authority. In this study using a normative juridical research method (legal research) Abstrak Tujuan penelitian ini untuk mengetahui dan menganalisis Pengenaan Bea Perolehan Hak atas Tanah dan Bangunan (BPHTB) pada program Pendaftaran Tanah Sistematis Lengkap (PTSL) dan Mekanisme Peralihan Sertipikat Hak Milik Pendaftaran Tanah Sistematis Lengkap (PTSL) menjadi Hak Tanggungan apabila Sertipikat Hak Milik diagunkan ke Bank. Rumusan Masalah, Bagaimana Pengenaan Bea Perolehan Hak atas Tanah dan Bangunan (BPHTB) pada program Pendaftaran Tanah Sistematis Lengkap (PTSL)? Dan Mekanisme Peralihan Sertipikat Hak Milik Pendaftaran Tanah Sistematis Lengkap (PTSL) menjadi Hak Tanggungan apabila Sertipikat Hak Milik diagunkan ke Bank? Menggunakan teori kepastian hukum, dan teori kewenangan.